Altered Jagged1-Notch1 Signaling in Enhanced Dysfunctional Neovascularization and Delayed Angiogenesis After Ischemic Stroke in HFD/STZ Induced Type 2 Diabetes Rats - Guo, Zhihui; Jia, Jia; Tu, Yanling; Jin, Chang; Guo, Cen; Song, Feifei; Wu, Xuqing; Bao, Haifeng; Fan, Wei (Frontiers in Physiology, 2021)
Diabetes exacerbates brain damage in cerebral ischemic stroke. Our previous study has demonstrated that after cerebral ischemia, type 2 diabetes rats displayed worse neurological outcomes, larger cerebral infarction and severer blood-brain barrier disruption. However, our knowledge of the mechanisms of how diabetes impacts the cerebrovascular repair process is limited. This study was aimed to characterize structural alterations and potential mechanisms in brain microvessels before and after ischemic stroke in type 2 diabetic rats treated with high-fat diet and streptozotocin (HFD/STZ). Furtherly, we tested our hypothesis that dysregulated intercellular Jagged1-Notch1 signaling was involved in the dysfunctional cerebral neovascularization both before and after ischemic stroke in HFD/STZ rats. In our study, we found increased yet dysfunctional neovascularization with activated Jagged1-Notch1 signaling in the cerebrovasculature before cerebral ischemia in HFD/STZ rats compared with non-diabetic rats. Furthermore, we observed delayed angiogenesis as well as suppressed Jagged1-Notch1 signaling after ischemic stroke. Our results elucidate the potential mechanisms underlying diabetes-related cerebral microvasculature dysfunction after ischemic stroke.